Construction and deconstruction of the historic garden concept - Andrade, Inês El-Jaick (Risco - Journal of Architecture and Urbanism, 2008)
This work emphasizes the relevance of the historical gardens as the expression of a historically produced environment. It analyzes and contextualizes this new heritage category considering its temporality and the integrity of its permanency. This work assumes that those" living monuments" are cultural documents that should rejuvenate and deteriorate, and that their uncompromised appropriation puts in risk their meaning and future testimony.